Biophysical and biochemical changes in skin health of healthcare professionals using respirators during COVID‐19 pandemic. Issue 1 (16th November 2022) - Abiakam, Nkemjika; Jayabal, Hemalatha; Mitchell, Kay; Bader, Dan; Worsley, Peter
Abstract: Background: Personal protective equipment, including respirator devices, has been used to protect healthcare workers (HCWs) during the COVID‐19 pandemic. These are fitted to skin sites on the face to prevent airborne transmission but have resulted in reports of discomfort and adverse skin reactions from their continued usage. The present study addresses the objective changes in both the structural integrity and biological response of the skin following prolonged and consecutive use of respirators. Materials and methods: A longitudinal cohort study, involving 17 HCWs who wear respirators daily, was designed. Changes in the barrier properties and biological response of the skin were assessed at three facial anatomical sites, namely, the nasal bridge, left cheek and at a location outside the perimeter of respirator. Assessments were made on three different sessions corresponding to the first, second and third consecutive days of mask usage. Skin parameters included transepidermal water loss (TEWL), stratum corneum (SC) hydration and erythema, as well as cytokine biomarkers sampled from sebum using a commercial tape. Results: The cheek and the site outside the perimeter covered by the respirator presented minimal changes in skin parameters. By contrast, significant increases in both the TEWL (up to 4.8 fold) and SC hydration (up to 2.7 fold) were detected at the nasal bridge on the second consecutive day of respirator‐wearing. There was a high degree of variation in the individual expression of pro‐and anti‐inflammatory cytokines. Increasing trends in nasal bridge TEWL values were associated with the body mass index ( p  < 0.05). Conclusions: The most sensitive objective parameter in detecting changes in the skin barrier proved to be the increase in TEWL at the nasal bridge, particularly on the second day of consecutive respirator usage. By contrast, other measures of skin were less able to detect remarkable variations in the barrier integrity. Consideration for protecting skin health is required for frontline workers, who continue to wear respirators for prolonged periods over consecutive days during the pandemic.